Expression profiles and prognostic significance of AFTPH in different tumors. Issue 12 (28th October 2020) - Zhu, Tengjiao; Chen, Yingtong; Liu, Zhongjun; Leng, Yuxin; Tian, Yun
Abstract : Aftiphilin (AFTPH) plays an important role in regulating intracellular trafficking, exocytosis, and the pro‐inflammatory response. However, the potential prognostic role of AFTPH in cancers remains unclear. Here, we examined the expression profiles and prognostic significance of AFTPH in breast invasive carcinoma (BRCA), diffuse large B‐cell lymphoma (DLBC), lung squamous cell carcinoma (LUSC), and pancreatic adenocarcinoma (PADD) using the GEPIA and UALCAN databases. AFTPH expression was observed to be higher in cancer tissues than in normal tissues, but expression did not differ significantly between tumor stages for the four cancer types. AFTPH expression in cancer cell lines was investigated using the CCLE database; AFTPH was found to be highly expressed in four cancer cell lines. The relationship between AFTPH expression and patient prognosis was analyzed using GEPIA, LinkedOmics, and Kaplan–Meier plotter databases. Low expression of AFTPH was associated with improved prognosis for BRCA, DLBC, LUSC, and PAAD. Genetic alterations of AFTPH in cancers were explored using the cBioPortal website, revealing that gene copy number gains and amplification are common in BRCA, DLBC, LUSC, and PAAD. Related genes and markers associated with AFTPH were discovered using the LinkedOmics database. Furthermore, transfection of cells with AFTPH siRNA demonstrated that AFTPH exerts positive effects on cell proliferation in BRCA, LUSC, and PAAD cells. In conclusion, AFTPH may be a potential therapeutic target and prognostic biomarker for BRCA, DLBC, LUSC, and/or PAAD. Abstract : Aftiphilin (AFTPH) plays an important role in regulating intracellular trafficking, exocytosis, and pro‐inflammatory response. The potential role of AFTPH in cancers remains unclear. This study was the first to comprehensively analyze the expression profiles and prognostic role of AFTPH in solid tumors and hematological malignancies, as well as providing evidence for subsequent studies on the molecular mechanism governing this role. AFTPH was suggested to be a potential therapeutic target and prognostic biomarker for BRCA, DLBC, LUSC, and PAAD.